More Critical Comments on Knowledge-Based Theories of the Firm - Foss, Nicolai J. (Organization Science, 1996)
This paper continues the critique of knowledge-based theories of the firm that was undertaken in Foss (Foss, N. J. 1996a. Knowledge-based approaches to the theory of the firm: Some critical comments. Organ. Sci. 7(5) 470–476.), specifically criticizing the reasoning in Kogut and Zander (Kogut, B., U. Zander. 1996. What firms do? Coordination, identity, and learning. Organ. Sci. 7(5) 502–518.) and Conner and Prahalad (Conner, K. R., C. K. Prahalad. 1996. A resource-based theory of the firm: Knowledge versus opportunism. Organ. Sci. 7(5) 477–501.). I argue that Kogut and Zander (Kogut, B., U. Zander. 1996. What firms do? Coordination, identity, and learning. Organ. Sci. 7(5) 502–518.) attempt to explain firm organization in terms of a preference for such organization—a distinctly non-economic mode of explanation—and that Conner and Prahalad fail to sufficiently characterize the nature of the firm, because they identify firm organization with the employment contract and neglect asset-ownership.